Grain and malt quality of selected winter barley genetic resources: ENG/CZ - Nesvadba, Zdeněk; Psota, Vratislav; Hartman, Ivo; Mařík, Pavel (KVASNY PRUMYSL, 2023)
The present study evaluated the agronomic and malting quality of 18 selected winter barley varieties. The varieties were obtained from the Gene Bank of the Crop Research Institute in Prague-Ruzyně. The varieties were tested under field conditions in three-year trials of basic evaluation. After the harvest, grain was malted and malting quality was determined according to international methods (EBC and MEBAK). The highest extract content was found in the Atlantick variety (80.6%). Proteolytic modification of the varieties Absolut, KWS Ariane and the line QK19/08030A_18 was at an optimal level. Values of diastatic power were high in all varieties, which is typical for winter barley varieties, similarly as low levels of cell wall degradation (friability) and high β-glucan content in the sweet wort. The lowest β-glucan content in the sweet wort was recorded in the two-row winter barley variety KWS Ariane (241 mg/l). Of the six-row varieties, the line QK19/08030A_18 had the lowest β-glucan content in the sweet wort (382 mg/l).